Legal Certainty in the Enforcement of Online Defamation Following the 2024 Reform of Indonesia's Electronic Information and Transactions Law - Sutikni Sutikni; Femmy Silaswaty; Ida Aryati (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid expansion of social media has increased online defamation cases and intensified legal uncertainty due to divergent interpretations of Indonesia’s Electronic Information and Transactions (ITE) Law. This study examines the legal boundaries of online defamation under Law Number 1 of 2024 and evaluates its enforcement from the perspective of legal certainty. Using a normative legal research method, the study applies statutory, conceptual, and case-based approaches through the analysis of legislation, legal doctrines, and judicial decisions. The findings show that Article 27A enhances legal certainty by clarifying the constituent elements of the offense, reaffirming the lex specialis derogat legi generali principle, and balancing the protection of reputation with freedom of expression. Effective enforcement requires clear legal norms, consistent judicial interpretation, adequate digital competence among law enforcement authorities, and harmonized institutional practices. The reform represents a significant step toward strengthening legal certainty in addressing online defamation.